Tackling antimicrobial resistance across sub-Saharan Africa: current challenges and implications for the future. Issue 8 (3rd August 2022) - Godman, Brian; Egwuenu, Abiodun; Wesangula, Evelyn; Schellack, Natalie; Kalungia, Aubrey Chichonyi; Tiroyakgosi, Celda; Kgatlwane, Joyce; Mwita, Julius C.; Patrick, Okwen; Niba, Loveline Lum; Amu, Adefolarin A.; Oguntade, Racheal Tomilola; et al.
ABSTRACT: Introduction: Antimicrobial resistance (AMR) is a concern as this increases morbidity, mortality, and costs, with sub-Saharan Africa having the highest rates globally. Concerns with rising AMR have resulted in international, Pan-African, and country activities including the development of national action plans (NAPs). However, there is variable implementation across Africa with key challenges persisting. Areas covered: Consequently, there is an urgent need to document current NAP activities and challenges across sub-Saharan Africa to provide future guidance. This builds on a narrative review of the literature. Expert Opinion: All surveyed sub-Saharan African countries have developed their NAPs; however, there is variable implementation. Countries including Botswana and Namibia are yet to officially launch their NAPs with Eswatini only recently launching its NAP. Cameroon is further ahead with its NAP than these countries; though there are concerns with implementation. South Africa appears to have made the greatest strides with implementing its NAP including regular monitoring of activities and instigation of antimicrobial stewardship programs. Key challenges remain across Africa. These include available personnel, expertise, capacity, and resources to undertake agreed NAP activities including active surveillance, lack of focal points to drive NAPs, and competing demands and priorities including among donors. These challenges are being addressed, with further co-ordinated efforts needed to reduce AMR.